PERANCANGAN PEMBANGKIT MIKROHIDRO PADA SALURAN PDAM MATA AIR LEWAJA KABUPATEN ENREKANG SULAWESI SELATAN - Ismuharram Ismuharram; Irawati Irawati; Ria Gazali (Institut Teknologi dan Bisnis Swadharma, 2022)
Electrical energy has become a part of our life. In fact, for some people it has become a major need that cannot be eliminated. This can affect the energy sources used in the power generation process. Therefore, the existence of renewable energy sources is needed to increase the energy supply for the community. In this case the author tries to do research to take advantage of the water discharge at the Lewaja Spring PDAM, Enrekang Regency, South Sulawesi as a Micro Hydro Power Plant (PLTMH). apipa, so that production costs can be reduced. In addition, it can provide an overview to the PDAM and the community that the PDAM pipes, which so far have only been used for water distribution, can be used as power plants. The purpose of this research is to determine the discharge and pipe head of PDAM and then the dimensional design of the turbine is based on the potential obtained. The survey was conducted to obtain primary data and secondary data. the main data is data obtained directly, while secondary data is data obtained from documents stored in PDAM Lewaja Springs. From the research, the average discharge is 46,287 L/s under normal conditions, and has a water level of 5,998 m from the turbine location